Showing the Spirit a theological exposition of 1 Corinthians 12-14 - Carson, Don A.; Moore Theological College lectures, Sydney, Australia, 1985. (Homebush West, NSW Lancer, 1988)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Corinthians, 1st, XII-XIV -- criticism, interpretation, etc; Pentecostalism -- controversial literature